High temperature vapour-liquid equilibria of water-polyalcohol mixtures - Cristino, Ana Filipa Russo De Albuquerque (2015)
Tese de doutoramento, Química (Química Tecnológica), Universidade de Lisboa, Faculdade de Ciências, 2014